2006
DOI: 10.17221/3451-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liming on the microbial biomass and its activities in soils long-term contaminated by toxic elements

Abstract: The effects of liming by CaO and CaCO 3 on soil microbial characteristics were studied during laboratory incubation of long-term contaminated arable and grassland soils from the vicinity of lead smelter near Příbram (Czech Republic). The CaO treatment showed significant negative effects on soil microbial biomass C and its respiratory activity in both studied soils, despite the fact that microbial biomass C in the grassland soil increased sharply during the first day of incubation. The metabolic quotient (qCO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This has led to improvement of soil fertility in limed sites compared to unlimed areas [1416]. Relationship between soil pH and its effect on the activity and composition of microbial populations have been discussed in various reports [4,6,810,1719]. Low pH inhibits the growth of soil bacteria in favor of more resistant fungi [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…This has led to improvement of soil fertility in limed sites compared to unlimed areas [1416]. Relationship between soil pH and its effect on the activity and composition of microbial populations have been discussed in various reports [4,6,810,1719]. Low pH inhibits the growth of soil bacteria in favor of more resistant fungi [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggest that increasing soil pH by liming reduces soil fungal populations and at the same time improves bacterial growth (Alabouvette 1999; Muhlbachova and Tlustos 2006;Scher and Baker 1980). According to our observations, liming with CaCO3 had a significant reduction effect on root rot of soybean caused by Fg during a four-week period.…”
Section: Discussionsupporting
confidence: 77%
“…This difference may be due to the different adsorption rates of Ca 2+ from the two different liming materials onto the colloidal complex, increasing base saturation and ultimately increasing soil pH. Lyngstad [23] found an increase in N mineralisation over a 3-year period as a result of adding CaCO 3 lime, whilst Mühlbachová and Tlustoš [24] found that although soil microbial activity initially decreased after application of CaO compared to CaCO 3 in the first days of incubation, CaO ultimately caused rapid mineralisation of the organic matter compared to CaCO 3 . Alternatively, the difference in the mineralisation of N between these two products may be due to water soluble Ca 2+ from LAB stimulating microbial aggregation within the soil matrix soon after incorporation, subsequently accelerating decomposition and mineralisation of N. Mahoney et al [25] found evidence of microbial aggregation when lime was added to an anaerobic sludge digester.…”
Section: Resultsmentioning
confidence: 99%